Plan estratégico de marketing para la empresa auto decoraciones super car de la ciudad de Loja - Villegas León, Jorge Luis (2016)
The development of this work has as main objective the development of "STRATEGIC MARKETING FOR SUPER CAR COMPANY OF AUTO DECORATIONS Loja", for this purpose the methods deductive, inductive, descriptive, analytical synthetic, mathematical and statistical; and direct techniques, literature and surveys observation, the same as those applied to 304 customers, sampled 1258 which customers were billed prior to the implementation date of the polls, in the same way, He applied to a total of 5 employees and the owner manager. The study began with the situational analysis, in which both the external environment and internal analyzed. In the external environment factors such as political, economic, cultural and technological partner as well as the five forces of Michael Porter analyzed, where was obtained as major opportunities for Auto company decorations Super Car the new trend and tastes for cars added to the variety of providers out there today, the threat of which the largest are temporarily competition and tariff rate on imports, that raise certain products was also defined; The analysis of external factors matrix EFE, determined a value of 2.26, indicating that the company is in an unfavorable environment where threats on opportunities predominate. For the analysis of the internal factors we proceeded with the implementation of customer surveys of the company, its employees and to Jorge Luis Villegas Manager, the information collected allowed the construction of the evaluation matrix EFI Internal factors in where six strengths that stand between the customer loyalty and good relationship between those who make Super Car was determined, and 6 weaknesses, which weighs more advertising is low, giving a score of 2.54, meaning that there is slight predominance of strengths over weaknesses. Then we proceeded to the development of the SWOT matrix, at the intersection of the variables were 4 strategic objectives, which are broken down into the discussion, as introduction to the draft strategic marketing plan. Finally a budget to each of the strategic objectives where the costs with estimated values of the environment is established, which make investment value realized that allow decorations Super Car Auto strengthen its image in the market and consequently improve profitability.